2005
DOI: 10.1021/jm050008p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Small, Membrane-Permeant, Caspase-Activatable Far-Red Fluorescent Peptide for Imaging Apoptosis

Abstract: To image apoptosis in vivo with a small, membrane-permeant probe, TcapQ(647) was synthesized comprising a Tat-peptide-based permeation peptide sequence, an effector caspase recognition sequence, DEVD, and a flanking optically activatable pair comprising a far-red quencher, QSY 21, and a fluorophore, Alexa Fluor 647. Under baseline conditions, high quenching efficiencies were observed resulting in low background fluorescence. Upon exposure to executioner caspases, TcapQ(647) was specifically cleaved, thereby re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(137 citation statements)
references
References 14 publications
4
132
1
Order By: Relevance
“…This probe is identical to that of TcapQ, except that the entire peptide, including the DEVD cleavage sequence, consists entirely of nonnative d, as opposed to l, amino acids. In vitro experiments have previously confirmed that the all-d probe is not activated by effector caspases (19). Eyes in which dTcapQ were injected following NMDA injection showed little to no fluorescent labeling in the retina (data not shown), consistent with stereospecific probe activation by effector caspases in vivo.…”
Section: Injection Of Noncleavable Dtcapq To Rule Out Nonspecific Probesupporting
confidence: 55%
See 1 more Smart Citation
“…This probe is identical to that of TcapQ, except that the entire peptide, including the DEVD cleavage sequence, consists entirely of nonnative d, as opposed to l, amino acids. In vitro experiments have previously confirmed that the all-d probe is not activated by effector caspases (19). Eyes in which dTcapQ were injected following NMDA injection showed little to no fluorescent labeling in the retina (data not shown), consistent with stereospecific probe activation by effector caspases in vivo.…”
Section: Injection Of Noncleavable Dtcapq To Rule Out Nonspecific Probesupporting
confidence: 55%
“…The in vitro and preliminary in vivo validation of a cell-penetrating effector caspase imaging probe, TcapQ, has been previously described (18,19). This probe utilizes a modified Tat peptide cell-penetrating moiety, which confers a surprisingly selective uptake by RGCs following intravitreal injection (20).…”
mentioning
confidence: 99%
“…Bullok & Piwnica-Worms [41] developed a near-IR probe for caspase-3 to image apoptosis and showed successful application in vitro and in vivo. The C-terminal side of caspase-3 substrate was tagged with Alexa Fluor 647 as the energy donor, and the quencher QSY21 as the energy acceptor was placed at the N-terminal side of the substrate.…”
Section: (D) Substrate Reporter Based On Fluorescence Resonance Energmentioning
confidence: 99%
“…In one study a construct containing the TAT-PTD sequence, a tetrapeptide from the amino side of a target recognition/cleavage site, and both a donor and a quencher was synthesized as a probe for proteases inside live cells [19]. The TAT-PTD is believed to transport macromolecules into cells by an initial interaction with cell membrane lipid rafts in a receptor-independent manner, followed by a rapid internalization through macropinocytosis, then a pH drop and destabilization of the integrity of the macropinosome vesicle lipid bilayer, and, ultimately, release of the TATcargo into the cytosol [20].…”
Section: Approaches To Protease Probe and Inhibitor Designmentioning
confidence: 99%